A Survey of Nurses Knowledge Regarding Prevention and Management of Diabetic Foot Ulcer in Bangladesh (BIRDEM Medical Journal, 2014)
Diabetic foot ulcer is a preventable complication of diabetes. Nurses must have knowledge related to this condition so that education can be given to patients. This study aims to examine the level of nurses knowledge regarding prevention and management of diabetic foot ulcer in Bangladesh. A survey involved 218 nurses working at a national, specialized, and well-established institute of diabetic care of Bangladesh. The Nurses Knowledge Regarding Prevention and Management of Diabetic Foot Ulcer Questionnaire (NKPMDFUQ) comprising of 40 questions with 20 true/false questions and 20 multiple choice questions was used. It was content validated and tested for internal consistency and stability yielding acceptable levels of reliability. The findings revealed that nurses had very low level of knowledge (M=52.60%, SD=7.86%). The content areas most nurses did not have knowledge were detecting loss of protective sensation of the feet, caring of callus formation, encouraging patients to have activity of daily living in order to self-manage, setting a goal for prevention of amputation, and giving advice to patients that causes of diabetes is the least important element in diabetic foot care program. The findings are beneficial for establishing training courses. Consequently, quality of care for patients with diabetes will be improved. DOI: http://dx.doi.org/10.3329/birdem.v4i1.18549 Birdem Med J 2014; 4(1): 22-26